Estimating Trade Restrictiveness Indices - Kee, Hiau Looi; Nicita, Alessandro; Olarreaga, Marcelo (World Bank, Washington, DC, 2012)
The objective of this paper is to provide indicators of trade restrictiveness that include both measures of tariff and nontariff barriers for 91 developing and industrial countries. For each country, the authors estimate three trade restrictiveness indices. The first one summarizes the degree of trade distortions that each country imposes on itself through its own trade policies. The second one focuses on the trade distortions imposed by each country on its import bundle. The last index focuses on market access and summarizes the trade distortions imposed by the rest of the world on each country's export bundle. All indices are estimated for the broad aggregates of manufacturing and agriculture products. Results suggest that poor countries (and those with the highest poverty headcount) tend to be more restrictive, but they also face the highest trade barriers on their export bundle. This is partly explained by the fact that agriculture protection is generally larger than manufacturing protection. Nontariff barriers contribute more than 70 percent on average to world protection, underlying their importance for any study on trade protection.